1989
DOI: 10.1148/radiology.173.2.2678246
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between image quality and ultrasound exposure level in diagnostic US devices.

Abstract: Ultrasonographic B-mode images were obtained at various exposure levels with three real-time diagnostic scanners. Adult human and tissue-equivalent phantom images were compared in terms of diagnostic content and depth of penetration. For the exposure level settings used, spatial-peak pulse-average intensities ranged from approximately 10 to 500 W/cm2. At the 3.50-3.75-MHz nominal frequencies used in the study, images of the human abdomen showed little discernible change in quality with varying exposure levels.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

1995
1995
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 0 publications
0
4
0
2
Order By: Relevance
“…Although no previous study has assessed the relationship between TIB and ultrasound intensity, previous papers have pointed out various limitations of TI 22,[27][28][29] . One previous study examined the effect of output power settings on image quality, and found considerable discrepancy in I SPTA.3 values between scanners with similar output power settings 30 . That study, however, predates TI, so no direct comparisons could be made.…”
Section: Discussionmentioning
confidence: 99%
“…Although no previous study has assessed the relationship between TIB and ultrasound intensity, previous papers have pointed out various limitations of TI 22,[27][28][29] . One previous study examined the effect of output power settings on image quality, and found considerable discrepancy in I SPTA.3 values between scanners with similar output power settings 30 . That study, however, predates TI, so no direct comparisons could be made.…”
Section: Discussionmentioning
confidence: 99%
“…Der Vorteil einer sicheren und umsichtigen sonografischen Bildgebung in der Schwangerschaft besteht darin, dass der Ultraschalluntersucher und die schwangere Frau sicher sein können, dass klinisch relevante Informationen gewonnen werden, während das Risiko für mögliche negative Bioeffekte auf ein Minimum reduziert wird. Die Einschränkung besteht darin, dass eine reduzierte Leistungseinstellung die Bildqualität beeinträchtigen kann, obwohl Studien darauf hinweisen, dass dieser Effekt vernachlässigbar ist [21,22]. Eine reduzierte Ausgangsleistung sollte den Benutzer ermutigen, Frequenz, Fokus, Gain und Zoom aktiv anzupassen, um die Bildqualität zu the exposure to high-intensity modalities, such as Doppler, should be used only for as long as needed.…”
Section: Vorteile Und Grenzen Der Ultraschallbildgebungunclassified
“…The advantages of safe and prudent ultrasound imaging of the neonate are that the ultrasound examiner and the parents may rest assured that clinically relevant information is being obtained while the risk for potential negative bioeffects is being kept to a minimum. The limitation is that a reduced power output setting may decrease image quality, although studies indicate that this effect is negligible [21,22]. A reduced output power may even encourage the user to actively adjust frequency, focus, gain, and zoom to optimize image quality, thus achieving better diagnostic imaging.…”
Section: Advantages and Limitations Of Ultrasound Imagingmentioning
confidence: 99%
“…Fourth, there is some evidence that any positive temperature differential for any period of time may have some effect, in other words that there may be no threshold for hyperthermia‐induced birth defects29. Fifth, there is a possibility of further relaxing or completely eliminating present FDA regulations on the premise that greater acoustic outputs would improve diagnostic capability under certain circumstances30, although this, in reality, is entirely unproven31. Finally, there is disquieting data indicating that practitioners are generally unaware not only of the TI, including its meaning and utility, but also of the MI and of bioeffects and safety‐of‐ultrasound issues, in general32, 33.…”
Section: What Is the Issue Why Are Scientists Studying It And Why Domentioning
confidence: 99%